2004
DOI: 10.1523/jneurosci.2971-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fear Memory Reconsolidation

Abstract: Reactivation of consolidated memories returns them to a protein synthesis-dependent state. One interpretation of these findings is that the memory reconsolidates after use. Two alternative interpretations are that protein synthesis inhibition facilitates extinction and that postreactivation protein synthesis inhibition leads to an inability to retrieve the consolidated memory. First, using two different approaches, we report that reconsolidation cannot be reduced down to facilitated extinction. We show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
296
2
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(327 citation statements)
references
References 37 publications
25
296
2
4
Order By: Relevance
“…Thus, our data confirm that the effects of Zif268 ASO on the impairment of appetitive and aversive memory reconsolidation are reactivation dependent (Lee et al, 2005(Lee et al, , 2006Debiec et al, 2006). Some studies have demonstrated a recovery from amnesia after reconsolidation blockade with repeated testing (Lattal and Abel, 2004;Power et al 2006), whereas others have found no evidence of recovery (Duvarci and Nader, 2004;Lee et al, 2004). Although the current study did not test for persistent impairments in heroin seeking, previous data from our laboratory using Zif268 ASOs to explore both appetitive and aversive memory reconsolidation deficits have never observed any indication of a recovery, suggesting a persistent amnesia after this manipulation (Lee et al, 2004(Lee et al, , 2005(Lee et al, , 2006.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, our data confirm that the effects of Zif268 ASO on the impairment of appetitive and aversive memory reconsolidation are reactivation dependent (Lee et al, 2005(Lee et al, , 2006Debiec et al, 2006). Some studies have demonstrated a recovery from amnesia after reconsolidation blockade with repeated testing (Lattal and Abel, 2004;Power et al 2006), whereas others have found no evidence of recovery (Duvarci and Nader, 2004;Lee et al, 2004). Although the current study did not test for persistent impairments in heroin seeking, previous data from our laboratory using Zif268 ASOs to explore both appetitive and aversive memory reconsolidation deficits have never observed any indication of a recovery, suggesting a persistent amnesia after this manipulation (Lee et al, 2004(Lee et al, , 2005(Lee et al, , 2006.…”
Section: Discussionsupporting
confidence: 85%
“…Accumulated experimental data support the argument that after retrieval, consolidated memory may become temporarily vulnerable to disruption for a limited period of time (Przybyslawski and Sara, 1997;Przybyslawski et al, 1999;Nader, 2003;Debiec and Ledoux, 2004;Duvarci and Nader, 2004). Such vulnerability is followed by a stabilization processFusually referred to as reconsolidationFthat requires de novo protein synthesis.…”
Section: Introductionmentioning
confidence: 70%
“…Extinction is a process by which a new inhibitory association is formed following a longer exposure to a CS, resulting in a reduced fear response (Myers and Davis, 2002). Previous studies suggest that the basolateral nucleus of the amygdala (BLA) is mainly involved in reconsolidation (Nader et al, 2000;Duvarci and Nader, 2004;Baldi et al, 2008), and that the amygdala, hippocampus, and medial prefrontal cortex (mPFC) form a circuit necessary for extinction in rodents (for review, see Corcoran and Quirk, 2007;Sotres-Bayon et al, 2004;Quirk and Mueller, 2008).…”
Section: Introductionmentioning
confidence: 99%